1996
DOI: 10.1002/(sici)1097-4547(19960215)43:4<465::aid-jnr7>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Removal of serum from primary cultures of cerebellar granule neurons induces oxidative stress and DNA fragmentation: Protection with antioxidants and glutamate receptor antagonists

Abstract: Cerebellar granule neurons undergo apoptosis when deprived of chronic depolarization; serum deprivation has not been considered as a trigger of apoptosis in this culture. Here we report that serum removal triggers cell injury, which is characterized by signs of apoptosis. Actual cell death (trypan blue permeability) occurred 24 and 48 hr after serum removal. At earlier times (6 and 8 hr after serum removal) we found significant impairment of mitochondrial functioning [3‐(4,5‐dimethyl thiazol‐2‐yl)‐2,5‐diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(44 citation statements)
references
References 46 publications
(49 reference statements)
3
41
0
Order By: Relevance
“…Although the cells were gradually propagated to adapt to serum free media, it is well known that serum-deprived in vitro conditions predispose cells to oxidative cellular stress [54]. This type of cellular stress is characterized by the production of ROS that react with and damage fats, proteins, or DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cells were gradually propagated to adapt to serum free media, it is well known that serum-deprived in vitro conditions predispose cells to oxidative cellular stress [54]. This type of cellular stress is characterized by the production of ROS that react with and damage fats, proteins, or DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is one trigger of apoptotic cell death and treatment of cells with a variety of different exogenous antioxidants blocks apoptosis [5,7,8,44,45,[54][55][56]. However, it was demonstrated that hypertonic stress and mannitol could induce programmed cell death in vascular endothelial cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-oxidants and redox cycling agents [18][19][20][21] can induce apoptosis. Other apoptotic stimuli, such as treatment with TNF-α [22] lipopolysaccharide [23], growth factor withdrawal [24], and human immunodeficiency virus infection [25], can stimulate ROS production. Studies with TNF-α have shown that these agents activate ROS generation by mitochondria [22].…”
Section: Introductionmentioning
confidence: 99%